Herbal medicines use and associated factors among pregnant women in Debre Tabor town, north West Ethiopia: a mixed method approach - Getu Tesfaw Addis; Birhanu Demeke Workneh; Mesfin Haile Kahissay (BMC, 2021)
Abstract Background Use of herbal medicines during pregnancy has been increase in many developing and developed countries. In spite of the studies done on herbal medicine, no study has addressed use of herbal medicine among pregnant women in Debre Tabor Town. Hence, the major aim of this study was to assess the prevalence of herbal medicine use and associated factors. Methods A community based explanatory sequential mixed methods was employed. The quantitative method used cross-sectional study design with a sample size of 267 women, also 12 participants in a group for focus group discussion and 6 in-depth interviews from focus group were included for a qualitative part using a purposive sampling technique. The data were coded and entered into Epidata 4.2.0.0 and analysis was done using SPSS version 25, while thematic analysis was used for qualitative data. Bivariate and multivariate logistic analyses were used to assess associations between dependent and independent variables. Results Ninety-five (36.3%) of pregnant women used herbal medicine during pregnancy. Prior use of herbal medicine (AOR: 3.138; 95% CI: 1.375, 7.162), unable to read & write (AOR: 9.316; 95% CI: 2.339, 37.101), presence of health problems (AOR: 3.263; 95% CI: 1.502, 7.090), drug availability (AOR: 9.872; 95% CI: 4.322, 22.551) and distance to the health facilities (AOR 6.153; 95% CI 2.487, 15.226) were significantly associated with use of herbal medicine. Only 5(5.3%) of herbal medicine users disclosed their herbal medicine use to their healthcare providers. Zingiber officinale, Eucalyptus globulus, Rutachalepensis, Linumusitatissimum, and Moringa stenopetala were the most commonly used herbal medicines by pregnant women. Conclusions The use of herbal medicine during pregnancy is a common practice and significantly associated with educational status, prior use of herbal medicine, presence of health problems, drug availability and distance to the health facilities. Since there was high prevalence and low disclosure rate of herbal medicine use, it should be ensured that physicians/midwives establish a good level of communication with pregnant women.